2023
DOI: 10.1101/2023.08.25.23294606
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct COVID-19 vaccine combinations result in divergent immune responses

Luca M. Zaeck,
Ngoc H. Tan,
Wim J.R. Rietdijk
et al.

Abstract: Waning antibody responses after COVID-19 vaccination combined with the emergence of the SARS-CoV-2 Omicron lineage led to reduced vaccine effectiveness. As a countermeasure, bivalent mRNA-based booster vaccines encoding the ancestral spike protein in combination with that of Omicron BA.1 or BA.5 were introduced. Since then, BA.2-descendent lineages have become dominant, such as XBB.1.5 or BA.2.86. Here, we assessed how different COVID-19 priming regimens affect the immunogenicity of the recently used bivalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
2
1
0
Order By: Relevance
“…This finding aligns with trials of the mRNA-1273.214 BA.1 bivalent vaccine, which was found to elicit superior NAb titers against its target antigen, Omicron BA.1, compared to the monovalent mRNA-1273 vaccine ( 15, 16 ). We also found that the BA.5 bivalent booster broadened variant NAb recognition the most, eliciting higher BA.5 NAb titers than the BA.1 bivalent and monovalent boosters, which confirms previous findings for this vaccine ( 14, 15, 38–40 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This finding aligns with trials of the mRNA-1273.214 BA.1 bivalent vaccine, which was found to elicit superior NAb titers against its target antigen, Omicron BA.1, compared to the monovalent mRNA-1273 vaccine ( 15, 16 ). We also found that the BA.5 bivalent booster broadened variant NAb recognition the most, eliciting higher BA.5 NAb titers than the BA.1 bivalent and monovalent boosters, which confirms previous findings for this vaccine ( 14, 15, 38–40 ).…”
Section: Discussionsupporting
confidence: 90%
“…The WH1, BA.1, and BA.5 NAb titers of the bivalent vaccine recipients in our report displayed similar patterns as those from the SWITCH-ON trial ( 30, 38 ). We here extended these findings to report that both bivalent boosters elicited greater antibody responses than a monovalent booster, resulting in higher BA.1 and BA.5 NAb titers.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation